2022
DOI: 10.3390/ph15091049
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin in the Prevention and Treatment of Coronavirus Infections: A Focus on SARS-CoV-2

Abstract: The COVID-19 outbreak seems to be the most dangerous challenge of the third millennium due to its highly contagious nature. Amongst natural molecules for COVID-19 treatment, the flavonoid molecule quercetin (QR) is currently considered one of the most promising. QR is an active agent against SARS and MERS due to its antimicrobial, antiviral, anti-inflammatory, antioxidant, and some other beneficial effects. QR may hold therapeutic potential against SARS-CoV-2 due to its inhibitory effects on several stages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 114 publications
1
39
0
2
Order By: Relevance
“…When cytokine storm hits, the afflicted victims die. A cytokine storm caused by a coronavirus can be prevented by several naturally occurring polyphenols, such as curcumin, apigenin, resveratrol, and kaempferol [70] , [71] , [72] , [73] , [74] . These findings suggest that edible antimicrobial coatings on fruits can help prevent virus transmission before infection, while also extending the shelf-life of polyphenolic fruits, which are vital for the recovery of COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%
“…When cytokine storm hits, the afflicted victims die. A cytokine storm caused by a coronavirus can be prevented by several naturally occurring polyphenols, such as curcumin, apigenin, resveratrol, and kaempferol [70] , [71] , [72] , [73] , [74] . These findings suggest that edible antimicrobial coatings on fruits can help prevent virus transmission before infection, while also extending the shelf-life of polyphenolic fruits, which are vital for the recovery of COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Plant polyphenols are one of the most important categories of natural active principles with antioxidant effects, being increasingly used in skin antiaging therapy, having remarkable properties in combating the harmful effects of solar radiation and atmospheric pollutants, preventing and alleviating the symptoms of premature skin aging. Specifically, polyphenols are recognized for their antioxidant, anti-inflammatory, antibacterial, antiviral, antitumor, and anti-atherogenic action (against deposition on blood vessels) [ 116 , 117 ]. The main action of antioxidants is to prevent the formation of free radicals, fighting against aging processes.…”
Section: Plant Metabolitesmentioning
confidence: 99%
“…In another study, researchers reported that curcumin from turmeric and mustard plants is a source of a non-flavonoid polyphenol that can effectively suppress inflammatory mediators such as cyclooxygenase (COX) [ 47 , 48 , 49 ]. In addition to the PPs mentioned above, gingerol, caffeic acid, and quercetin can suppress severe inflammation [ 42 , 50 , 51 ]. Rodríguez-Ramiro et al reported that cocoa enriched with PPs and its bioactive properties could reduce severe inflammation effects such as intestinal inflammation and avoid associated cancer [ 52 ].…”
Section: Polyphenols In the Prevention And Treatment Of Different Met...mentioning
confidence: 99%